VILLAGE FISCAL TRANSFERS AND INTER-REGIONAL INEQUALITY REDUCTION: THE DYNAMICS OF VILLAGE DEVELOPMENT IN NORTH MALUKU - Muammil Sun’an; Said Mala; Abdul Chalid Ahmad; Irawan Abae (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of the number of developing villages, the village development index, village expenditure, and village literacy on village fiscal transfers in North Maluku Province. Using a panel data regression approach and a random effects model in nine districts/cities during the 2017-2024 period, this study found that village expenditure and village literacy levels did not significantly influence the amount of fiscal transfers received by villages. In contrast, village fiscal transfers showed a significant impact in reducing disparities between regions, especially in areas such as Central Halmahera Regency, Morotai Island, Tidore Islands City, and Taliabu Regency. These findings indicate that a fiscal approach based on region and village performance is more effective in promoting inclusive development in the archipelago. The results of this study provide important implications for the formulation of affirmative fiscal policies and strengthening village development governance in disadvantaged, frontier, and outermost (3T) regions.